Numerical and Experimental Research on the Effect of Platform Heave Motion on Vortex-Induced Vibration of Deep Sea Top-Tensioned Riser - Jie Zhang; Ying Zeng; Yougang Tang; Wenyun Guo; Zhenkui Wang (Shock and Vibration)
The prediction and control of vortex-induced vibration (VIV) is one of the key problems for riser design. The effect of platform heave motion on VIV of deep sea top-tensioned riser (TTR) is presented by means of numerical simulation and experiment in this research. First, the heave motion was modeled as a parametric excitation, and the governing equation of VIV of riser considering the parametric excitation was established. Then, the dynamic response of TTR was calculated numerically by the finite difference method based on the Van der Pol wake-oscillator model. Finally, a validation experiment was carried out at the towing tank of Tianjin university. The results show that the VIV response at the bottom of riser is significantly increased due to the platform heave motion, especially in the situation of low current velocity. The larger amplitude and the higher frequency of the platform heave motion with the greater influence are generated on VIV of TTR. In particular, the value of 0.5 times, 1 time, or other multiples of the platform heave frequency will be included in the vibration frequency component of TTR when the platform heave amplitude is large and the frequency is high.